Efisiensi Pengaturan Jadwal Perkuliahan Menggunakan Pendekatan Pewarnaan Graf - Syamsyida Rozi; Niken Rarasati; Rosda Syelly (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
The schedule for each course should be arranged such that the course taken by the same student or involving the same lecturer are not scheduled on the same day and time. This is to avoid conflicting schedules for students and lecturers. In the odd semester academic year 2021/2022, there were 23 courses scheduled at the study program of Mathematics, Universitas Jambi. The students in semesters 1 and 5 were divided into 2 classes, respectively, due to a large number of students in that semester. Therefore, the arrangement of the course schedule was getting more complicated. This research aimed to arrange the course schedule so that there is no clash by using the graph coloring approach. This research was classified as case study research and applied the descriptive method. The arrangement of the course schedule began with modeling the problem in the form of a graph and then using the Welch Powell algorithm to color the vertices in the graph. The graph consists of 36 vertices and 215 edges. By applying the Welch-Powell algorithm, the chromatic number obtained was 10, which means there are 10 optimum sessions or 10 minimum sessions of the course schedule in the odd semester in the Mathematics study program Universitas Jambi. Based on this result, the grouping of courses can be obtained that can be scheduled on the same day and at the same time.